Evolutionary origins of the lysosome-related organelle sorting machinery reveal ancient homology in post-endosome trafficking pathways - More, Kiran J; Kaufman, Jonathan G G; Dacks, Joel B; Manna, Paul T (Proceedings of the National Academy of Sciences of the United States of America, 2024)
The major organelles of the endomembrane system were in place by the time of the last eukaryotic common ancestor (LECA) (~1.5 billion years ago). Their acquisitions were defining milestones during eukaryogenesis. Comparative cell biology and evolutionary analyses show multiple instances of homology in the protein machinery controlling distinct interorganelle trafficking routes. Resolving these homologous relationships allows us to explore processes underlying the emergence of additional, distinct cellular compartments, infer ancestral states predating LECA, and explore the process of eukaryogenesis itself. Here, we undertake a molecular evolutionary analysis (including providing a transcriptome of the jakobid flagellate Reclinomonas americana), exploring the origins of the machinery responsible for the biogenesis of lysosome-related organelles (LROs), the Biogenesis of LRO Complexes (BLOCs 1,2, and 3). This pathway has been studied only in animals and is not considered a feature of the basic eukaryotic cell plan. We show that this machinery is present across the eukaryotic tree of life and was likely in place prior to LECA, making it an underappreciated facet of eukaryotic cellular organisation. Moreover, we resolve multiple points of ancient homology between all three BLOCs and other post-endosomal retrograde trafficking machinery (BORC, CCZ1 and MON1 proteins, and an unexpected relationship with the "homotypic fusion and vacuole protein sorting" (HOPS) and "Class C core vacuole/endosomal tethering" (CORVET) complexes), offering a mechanistic and evolutionary unification of these trafficking pathways. Overall, this study provides a comprehensive account of the rise of the LROs biogenesis machinery from before the LECA to current eukaryotic diversity, integrating it into the larger mechanistic framework describing endomembrane evolution.
Keywords: molekulární evoluce; Lysosomes; biologická evoluce; endozomy; transport proteinů; Eukaryota; BORC; molecular evolution; Organelles; lysosome-related organelle; Biological Evolution; fylogeneze; organely; lyzozomy; comparative genomics; Protein Transport; BLOC; Phylogeny; Endosomes; Evolution, Molecular